IDENTIFIKASI KANDUNGAN BAHAN KIMIA OBAT PARASETAMOL PADA JAMU ASAM URAT YANG BEREDAR DI KECAMATAN SUNGAI KUNJANG SAMARINDA - Henny Nurhasnawati; Rahmayulis -; Dery Ahlul Azmi (PROSIDING SEMINAR KIMIA, 2014)
This research about identifying medicine chemicals content of parasetamol on uric acid herb which found at Kecamatan Sungai Kunjang have been done. This research methods start with intake of sample, sample preparation and identify parasetamol through colour reaction and thin layer chromatography. Colour reaction use azo reagen, FeCl 3 10% and K 2 Cr 2 O 7 . While eluen for KLT use sikloheksana : chloroform : methanol : glacial acetic acid (60 : 30 : 5 : 5) and chloroform : methanol ( 90 : 10) Result of research show there are one sample which positive contain parasetamol that is B sample with value of Rf = 0,03 in first eluen and 0,24 in second eluen. While two sample A a nd C are not indicated containing parasetamol.